HER2 dimerization inhibitor pertuzumab: mode of action and clinical data in breast cancer - Harbeck, Nadia; Schneeweiss, Andreas (Breast care, 2013)
The humanized monoclonal antibody pertuzumab prevents the dimerization of HER2 with other HER receptors, in particular the pairing of the most potent signaling heterodimer HER2/HER3, thus providing a potent strategy for dual HER2 inhibition. It binds to the extracellular domain of HER2 at a different epitope than trastuzumab. Pertuzumab and trastuzumab act in a complementary fashion and provide a more complete blockade of HER2-mediated signal transduction than either agent alone. Phase II studies demonstrated that pertuzumab was generally well tolerated as a single agent or in combination with trastuzumab and/or cytotoxic agents, and implied an improved clinical efficacy of the combination of pertuzumab and trastuzumab in early and advanced HER2-positive breast cancer. Results of the pivotal phase III study CLEOPATRA in patients with HER2-positive metastatic breast cancer demonstrated that the addition of pertuzumab to first-line combination therapy with docetaxel and trastuzumab significantly prolonged progression-free and overall survival without increasing cardiac toxicity. Currently, the combination of both antibodies is being explored in the palliative setting as well as in the treatment of early HER2-positive breast cancer. Dual HER2 inhibition with the HER2 dimerization inhibitor pertuzumab and trastuzumab may change clinical practice in HER2-positive first-line metastatic breast cancer treatment.
Gesehen am 26.02.2021